BALEFUL EFFECTS OF THE COMMERCIAL BIRTH CONTROL PILLS AND FOCUS ON FRONTIER HERBAL CONTRACEPTIVES DEVOID OF SIDE EFFECTS EFFECTS OF PILLS CONTRARY HERBAL ("Conference on Universal Science Research 2023", 2024)
The present review encompasses the contraception, methods of contraception, hormonal or chemical birth control pills and the herbal products having contraceptive activity with their merits and demerits. The commercially available birth control pills are detrimental to women health, might be life-threatening sometimes. The detrimental effects posed by such pills are: fat deposition in the liver, kidney and uterus, prevention of metabolism and further conception, disruption of the epithelial layer of the uterus, irregular and painful menstruation, breast cancer and ultimately permanent infertility. This study will help us to view the undeniable baleful effects of the commercial birth control pills and thus will rush us to explore some herbal birth control pills that will be cheaper, having no side effects and might be effective for the sexes (male & female). A research work has already been conducted in this regard which might be an evolutionary step in this realm.